Voluntourism (Volunteer Tourism) Dynamics: Tourist Experience That Might Save the Bali Starlings - Adrian Agoes; Indah Nur Agustiani (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2021)
The FNPF, a non-profit organization, has made a one-of-a-kind initiative to save Bali starlings. The FNPF has incorporated volunteer tourism (voluntourism) into their Bali starling conservation project. The foundation has established a Bali starling conservation facility on the small island of Nusa Penida, Bali. Their activities are ranging from accommodating volunteer tourists from other countries to work and assisting in conservation activities. This paper intends to examine whether this voluntourism activity has a significant impact on the conservation of Bali starlings. Due to pandemic condition, this study had been conducted from a distance interview with the head of the Bali starling conservation activity in Nusa Penida. He also helped collecting data from the volunteers. According to the study's findings, volunteer tourism has an influence on Bali starling conservation. Despite the fact that the influence is indirect, it is considerably significant. As a result, voluntourism will continue to be implemented in Nusa Penida's Bali starling conservation efforts.